(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
For thousands of years, humans have developed technologies to preserve memory, externalizing it through artifacts that allow the preservation and transmission of knowledge beyond direct experience. This article examines the interactions between humans and objects, highlighting the concepts of technology, artifact, and interface as key elements in the externalization of memory. Furthermore, it proposes a theoretical-methodological framework that combines Actor-Network Theory (ANT), the Philosophy of Technology, and the Philosophy of Information to analyze the complexity of augmented memory in a context of flourishing artificial intelligence. As part of the analysis, a specific case is presented that illustrates the application of these theoretical assumptions: the transition from analog to digital photography. Likewise, the ethical and critical dimensions of digital technologies are addressed, analyzing their impact on culture, subjectivity, and social relations. This interdisciplinary approach allows us to understand digital memory as a dynamic system where human and non-human actors negotiate meanings and transform both collective and personal memory in the digital age.